2008
DOI: 10.1021/jm800388m
|View full text |Cite
|
Sign up to set email alerts
|

Novel Terphenyls and 3,5-Diaryl Isoxazole Derivatives Endowed with Growth Supporting and Antiapoptotic Properties

Abstract: A new study on terphenyl and diaryl-isoxazole and -isoxazoline derivatives, maintaining a common 3-adamantyl-4-hydroxyphenyl moiety, has been conducted to find compounds with growth supporting and antiapoptotic properties. Unexpectedly, diphenyisoxazole derivatives bearing a nitro group replacing the carboxylic function have been found with the highest cell protective activity within the series, in complete and in serum-free conditions. Inhibition of apoptosis induced by daunorubicin has also been observed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…42 Despite this drawback, these reactions have been employed in many medicinal chemistry programs, including the synthesis of o-, m-and p-terphenyl derivatives with anti-apoptotic activity. 17,18 Scheme 7 Sequential Suzuki Cross-coupling Reactions for the Synthesis of Unsymmetrical Acid-containing Terphenyls…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Despite this drawback, these reactions have been employed in many medicinal chemistry programs, including the synthesis of o-, m-and p-terphenyl derivatives with anti-apoptotic activity. 17,18 Scheme 7 Sequential Suzuki Cross-coupling Reactions for the Synthesis of Unsymmetrical Acid-containing Terphenyls…”
Section: Methodsmentioning
confidence: 99%
“…12,13 Perhaps unsurprisingly, these structures have been widely examined in medicinal chemistry programs. [14][15][16][17][18] This review will highlight different synthetic approaches to preparing this interesting and important class of molecules. Generally, synthesis of terphenyls can be classified as one of two methods: (i) aryl-aryl coupling reactions, typically by the reaction of dihalobenzene derivatives with aryl-metal nucleophiles, with or without catalysts; or (ii) using open chain precursor(s) to construct the aromatic rings via concerted or stepwise benzannulation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, search for novel synthetic platelet protective molecules with potential to combat against ROS-induced pathological conditions is essential in vascular pharmacology. In this context, we have made an attempt to synthesize novel isoxazole derivatives, as isoxazole moiety has been recognized to possess a wide range of biological properties such as, anticoagulant, antiviral, anti-apoptotic, and anti-inflammatory properties [21][22][23][24]. Apart from these, many of the isoxazole-based drugs such as sulfamethoxazole, cycloserine, and acivicin are being commercially used for various treatments [25].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we have made an attempt to synthesize novel isoxazole derivatives, as isoxazole moiety has been recognized to possess a wide range of biological properties such as, anticoagulant, antiviral, anti-apoptotic, and anti-inflammatory properties [21][22][23][24]. Apart from these, many of the isoxazole-based drugs such as sulfamethoxazole, cycloserine, and acivicin are being commercially used for various treatments [25]. Upon consideration of the above facts, a series of novel isoxazole molecules (4a-h) were synthesized, and for the first time, we have made an effort to explore the platelet protective property of isoxazole derivatives with calcium ionophore (A23187) as agonist to induce platelet apotosis as earlier studies have reported that A23187 enhances ROS mediated apoptosis in several cell lines including platelets [26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, compound A acts as a ligand for brain cholinergic channel receptors, compound B as a neuroprotective agent, compound C is a novel pharmacophoric fragment‐containing androgen receptor (AR) modulator, compound D as potent agonists of the human 5‐HT2 A and 5‐HT 2C receptor, compound E as NCX1 inhibitor, and compound F as a highly potent glutamate GR5 agonist . Moreover, isoxazole pharmacophores have antithrombic, antiviral, antiapoptotic, and antiparasitic activities. These special properties of isoxazole render them an attractive target for organic chemist Figure .…”
Section: Introductionmentioning
confidence: 99%